2015
DOI: 10.5114/pjp.2015.54960
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological factors influencing results of combined treatment in patients with laryngeal cancer

Abstract: The aim of the study was to assess the prognostic value of postoperative histopathological factors as well as the clinical usefulness of the modified risk score for recurrence. In a group of 197 patients with laryngeal cancer who underwent surgery followed by radiation therapy, partial resection was performed in 21.5% of patients and total resection in 78.5%. The majority of patients had T3 or T4 (74%) and N0 (63%) cancer. Macroscopically positive margins were reported in 10% of patients after partial resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…In the analyzed group of laryngeal cancer patients treated with combined therapy (surgery followed by adjuvant radiotherapy), after a 5-year follow-up period the following rates were observed: LC of 69%, DFS of 61%, and OS of 45%. The obtained outcomes are concordant with relevant literature reporting 5-year LC rates ranging from 63% to 94% pT2 [3,4,5,18]. Literature data shows that radiotherapy increases the effectiveness of combined treatment by 20-30% compared to surgery alone and by 10-40% compared to radiotherapy alone [18,19,20,21].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In the analyzed group of laryngeal cancer patients treated with combined therapy (surgery followed by adjuvant radiotherapy), after a 5-year follow-up period the following rates were observed: LC of 69%, DFS of 61%, and OS of 45%. The obtained outcomes are concordant with relevant literature reporting 5-year LC rates ranging from 63% to 94% pT2 [3,4,5,18]. Literature data shows that radiotherapy increases the effectiveness of combined treatment by 20-30% compared to surgery alone and by 10-40% compared to radiotherapy alone [18,19,20,21].…”
Section: Discussionsupporting
confidence: 87%
“…Although in head and neck cancer patients qualification criteria for postoperative radiotherapy have been well established for many years, when analyzed individually may fail to show prognostic significance. Earlier studies revealed that what affects the outcomes of multimodality treatment is a combination of several risk factors for nodal and/or local relapse [4,6,22]. Identification of laryngeal cancer relapse risk groups in surgically treated patients can have a considerable significance for improving treatment results by precise and individual adjustment of physical parameters of radiation therapy (including total dose, radiation technique, irradiated tissue volume as well as treatment time) [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations